2009
DOI: 10.1103/physrevlett.103.147204
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Ground State of Single and Coupled Permalloy Rectangles

Abstract: We have studied the magnetic domain structure in Permalloy rectangles that reveal flux-closure domain configurations. Arrays with varying spacing between the rectangles are investigated by scanning electron microscopy with polarization analysis as well as by micromagnetic simulation. In contrast to general expectation, rectangles in the flux-closure Landau state show significant coupling and form a magnetic pattern of common chirality. The coupling is due to the stray field that originates from small changes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…The cross-tie state is well described in the literature. 23 The vortex diamond state coincides with the described antivortex one up to interchanging of positions of vortices and antivortices, this state was already observed in rectangular [24][25][26] and elliptical 27 nanopaticles and also in mesoscopic islands of complicated form. 24 The quasicrystal state is very similar to the vortex-antivortex lattice recently predicted for wide films 10,11 .…”
supporting
confidence: 60%
“…The cross-tie state is well described in the literature. 23 The vortex diamond state coincides with the described antivortex one up to interchanging of positions of vortices and antivortices, this state was already observed in rectangular [24][25][26] and elliptical 27 nanopaticles and also in mesoscopic islands of complicated form. 24 The quasicrystal state is very similar to the vortex-antivortex lattice recently predicted for wide films 10,11 .…”
supporting
confidence: 60%
“…The second reason is that the Landau state creates stray fields that are caused by a slight tilting of the magnetization in the large domains out of the direction parallel to the long axis. 29,31 External fields along the short axis can easily affect that pre-existing tilting and increase the angle of tilt even at small fields. Hence, a magnetization tilting in the Landau structure occurs.…”
Section: B Hard-axis Magnetization Behaviormentioning
confidence: 99%
“…3 In microstructures it has been found that the sense of rotation of the vortex is affected by magnetic structures in the vicinity. [4][5][6][7] The ability to switch or set the sense of rotation and the polarity, i.e., the magnetization orientation of the vortex core, is a field of intense research. Recent publications demonstrate the possibility to change the sense of rotation in asymmetric single nanorings [8][9][10] and nanodisks 11 by applying external fields.…”
Section: Introductionmentioning
confidence: 99%